1997
DOI: 10.1007/s004250050085
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a soybean gene encoding cytosolic glutamine synthetase in shoots of transgenic Lotus corniculatus L. plants triggers changes in ammonium assimilation and plant development

Abstract: A soybean cytosolic glutamine synthetase gene (GS15) was fused with the constitutive 35S cauliflower mosaic virus (CaMV) promoter in order to direct overexpression in Lotus corniculatus L. plants. Following transformation with Agrobacterium rhizogenes, eight independent Lotus transformants were obtained which synthesized additional cytosolic glutamine synthetase (GS) in the shoots. To eliminate any interference caused by the T-DNA from the Ri plasmid, three primary transformants were crossed with untransformed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 37 publications
3
60
0
3
Order By: Relevance
“…In transformed plants placed under atmospheric Nfixing conditions, no differences were seen in the concentrations of sugars of the various plant parts, except that the free ammonium content of the nodules was reduced by approximately 50%. In addition, the amino acid content of the nodules was severely decreased due mostly to lower Asn content (Hirel et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In transformed plants placed under atmospheric Nfixing conditions, no differences were seen in the concentrations of sugars of the various plant parts, except that the free ammonium content of the nodules was reduced by approximately 50%. In addition, the amino acid content of the nodules was severely decreased due mostly to lower Asn content (Hirel et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Although a clear explanation of this spectacular effect could not be provided, results from this study showed that the increases in plant biomass followed the onset of symbiotic N fixation, which remained similar in the transgenic plants compared with the untransformed controls. After these observations, it was proposed that regulatory mechanisms, as yet unknown, control the balance between nodule GS activity and nodule biomass for optimal NUE and plant growth (Hirel et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poplar trees expressing a conifer GS gene were taller than the non-transformed trees under low nitrogen conditions and showed altered leaf morphology (Gallardo et al 1999;Fu et al 2003). A 50-80% increase in GS activity was detected in the leaves of Lotus corniculatus transformed with a soybean GS 1 gene driven by the CaMV 35S promoter (Vincent et al 1997). Pea plants transformed with a soybean GS 1 gene driven by the CaMV 35S promoter or a nodule-specific promoter, while showing increased levels of GS 1 , showed no increase in GS activity or in total nitrogen or protein content.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made to modulate the levels of the GS enzyme in different plants using genetic engineering tools, with rather mixed outcomes (Eckes et al 1989;Hemon et al 1990;Hirel et al 1992Hirel et al , 1997Temple et al 1993Temple et al , 1994Temple et al , 1998Su et al 1995;Vincent et al 1997;Brugiere et al 1999;Gallardo et al 1999;Limami et al 1999;Ortega et al 2001;Fuentes et al 2001;Oliveira et al 2002;Carvalho et al 2003;Fei et al 2003;Fu et al 2003;Harrison et al 2003). Tobacco plants transformed with different GS 1 genes driven by the CaMV 35S promoter have shown an increase in GS activity and GS 1 polypeptide level in the leaves (Eckes et al 1989;Hemon et al 1990;Hirel et al 1992Hirel et al , 1997Temple et al 1993;Fuentes et al 2001;Oliveira et al 2002).…”
Section: Introductionmentioning
confidence: 99%